A Pilot Study of Analysis of Students Cognition and Affection Styles in Strengthening Essay Writing Malay Language in Primary Schools - Perumal, Pushpavali; Husin, Mohd Razimi; Nachiappan, Suppiah (Archives of Business Research, 2022)
This study aims to analyze the cognition style and affections of students in writing Malay essays. The study sample involved 52 students Year 5 and 2 teacher to be interviewed. A total of 40 original essay texts were studied and analyzed and 12 students were interviewed to obtain data and transcribed into research texts. The text of this study was analyzed using Hermeneutic methods to interpret the findings of the study. Findings show that excellent and average students can apply cognition style, affective and past experience in essay writing while weak students face difficulties in practicing cognition style, affective and past experience